Stepping-motor-driven constant-shear-rate rotating viscometer - de Lucena, Samuel E. [UNESP]; Kaiser, Walter (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Despite the frequent use of stepping motors in robotics, automation, and a variety of precision instruments, they can hardly be found in rotational viscometers. This paper proposes the use of a stepping motor to drive a conventional constant-shear-rate laboratory rotational viscometer to avoid the use of velocity sensor and gearbox and, thus, simplify the instrument design. To investigate this driving technique, a commercial rotating viscometer has been adapted to be driven by a bipolar stepping motor, which is controlled via a personal computer. Special circuitry has been added to microstep the stepping motor at selectable step sizes and to condition the torque signal. Tests have been carried out using the prototype to produce flow curves for two standard Newtonian fluids (920 and 12 560 mPa (.) s, both at 25 degrees C). The flow curves have been obtained by employing several distinct microstep sizes within the shear rate range of 50-500 s(-1). The results indicate the feasibility of the proposed driving technique.
Keywords: computer-based instrumentation; microstepping; rotational viscometer; viscometer design; viscosity measurement